2021
DOI: 10.3390/ijms22073336
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Complement System on Human Endothelial Cells by Urban Particulate Matter Triggers Inflammation-Related Protein Production

Abstract: Exposure to particulate matter (PM) is becoming a major global health issue. The amount and time of exposure to PM are known to be closely associated with cardiovascular diseases. However, the mechanism through which PM affects the vascular system is still not clear. Endothelial cells line the interior surface of blood vessels and actively interact with plasma proteins, including the complement system. Unregulated complement activation caused by invaders, such as pollutants, may promote endothelial inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…The complement system is composed of complement inherent components, complement regulatory proteins and complement receptors [29]. Some proteins in complement receptors are expressed in vascular endothelial cells [30], while CD40 is expressed in B cells, mononuclear macrophages, dendritic cells and vascular endothelial cells [31].Therefore, we found that ES-PMMA bone cement reduce local thrombosis by regulating vascular endothelial CD40 protein expression.…”
Section: Cd40 Uorescence Staining Of Vascular Endothelial Cellsmentioning
confidence: 79%
“…The complement system is composed of complement inherent components, complement regulatory proteins and complement receptors [29]. Some proteins in complement receptors are expressed in vascular endothelial cells [30], while CD40 is expressed in B cells, mononuclear macrophages, dendritic cells and vascular endothelial cells [31].Therefore, we found that ES-PMMA bone cement reduce local thrombosis by regulating vascular endothelial CD40 protein expression.…”
Section: Cd40 Uorescence Staining Of Vascular Endothelial Cellsmentioning
confidence: 79%
“…While ROS can serve as signaling molecules to activate the host defense system against pathogens, excessive ROS production can lead to oxidative damage [ 62 ]. Several prior studies indicate that oxidative stress damages cells, leading to the release of DAMPs which activates the extracellular complement system through all three pathways [ 17 , 63 , 64 ]. It was demonstrated that exposure of urban particulate matter to human umbilical vein endothelial cells enhances ROS production and subsequent activation of the complement system via the alternative pathway [ 64 ].…”
Section: Role Of Mitochondrial Damps In Complement Responsementioning
confidence: 99%
“…Several prior studies indicate that oxidative stress damages cells, leading to the release of DAMPs which activates the extracellular complement system through all three pathways [ 17 , 63 , 64 ]. It was demonstrated that exposure of urban particulate matter to human umbilical vein endothelial cells enhances ROS production and subsequent activation of the complement system via the alternative pathway [ 64 ]. This observation was confirmed by inhibiting ROS production, which suppresses expression of retinol-binding protein 4/RBP4 and c-reactive protein/CRP, which are biomarkers of inflammation, indicating inhibited complement activation [ 64 ].…”
Section: Role Of Mitochondrial Damps In Complement Responsementioning
confidence: 99%
“…Inflammation is another critical mechanism affected by these pollutants [10,155,[175][176][177][178][179][180][181][182][183][184][185][186]. Chronic exposure to pollutants can trigger a sustained inflammatory response within the cardiovascular system and other organs as well.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%